2017
DOI: 10.1371/journal.pone.0174412
|View full text |Cite
|
Sign up to set email alerts
|

Maternal psychological responses during pregnancy after ultrasonographic detection of structural fetal anomalies: A prospective longitudinal observational study

Abstract: In this longitudinal prospective observational study performed at a tertiary perinatal referral centre, we aimed to assess maternal distress in pregnancy in women with ultrasound findings of fetal anomaly and compare this with distress in pregnant women with normal ultrasound findings. Pregnant women with a structural fetal anomaly (n = 48) and normal ultrasound (n = 105) were included. We administered self-report questionnaires (General Health Questionnaire-28, Impact of Event Scale-22 [IES], and Edinburgh Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
44
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 33 publications
7
44
0
2
Order By: Relevance
“…However, the predicted future severity of an anomaly detected in utero may vary throughout pregnancy as new diagnostic information could possibly be added to previous information. In previous research, we have, however, found that psychological distress in expectant mothers decreased from the time the fetal anomaly was diagnosed, to gestational week 36 (Kaasen et al, 2017).…”
Section: Introductionmentioning
confidence: 72%
“…However, the predicted future severity of an anomaly detected in utero may vary throughout pregnancy as new diagnostic information could possibly be added to previous information. In previous research, we have, however, found that psychological distress in expectant mothers decreased from the time the fetal anomaly was diagnosed, to gestational week 36 (Kaasen et al, 2017).…”
Section: Introductionmentioning
confidence: 72%
“…Two prospective single-centre studies assessed maternal anxiety using standardized assessments at various points after the diagnosis of a congenital anomaly and found state anxiety was the highest at the time of diagnosis (Aite et al, 2009;Kaasen et al, 2017). Within their longitudinal study, Kaasen et al (2017) reported the average score for the 48 participants reduced over the four-time points, although some women continued to meet the clinical threshold for anxiety at the final assessment at 36 weeks. Aite et al (2009) measured anxiety before and after consultation within two groups of pregnant women who had received prenatal diagnoses of lung malformations with a good prognosis (n = 21) or a life-threatening prognosis (n = 23).…”
Section: The Experience As Presented In the Literaturementioning
confidence: 99%
“…As mães padecem de um alto nível de sofrimento psicológico materno, após a detecção de uma anomalia fetal. Esse sofrimento pode diminuir durante a gravidez, de um nível inicial alto para um nível quase normal, porém os sintomas de depressão podem estar presentes até o final da gravidez 35 .…”
Section: O Diagnóstico De Anomalia Congênita Na Gestaçãounclassified